Analysis of Potential, Obstacles, and Strategies of Conventional and Electric Car Marketing - Ferdi Antonio; Nurlina; Elizabeth; Musran Munizu; Chanissa Purwaningrum (Indonesian Journal Economic Review (IJER), 2026)
The purpose of this study is to analyze the potential, obstacles, and strategies of conventional and electric car marketing. The analytical method in this study uses comprehensive analysis with the help of secondary data such as scientific books and journal articles from national and international journals. The research results show that the automotive market is currently in a very interesting transition period. On the one hand, conventional cars still dominate the roads thanks to their mature ecosystem. On the other hand, electric cars are emerging as the future of mobility, driven by sustainability issues and strict regulations. The main strategy for conventional cars should focus on the narrative of advanced fuel efficiency, engine reliability on all terrains, and ease of routine maintenance that is widespread even in remote areas. Conventional car manufacturers also need to package their campaigns by emphasizing the value of high functionality and unit readiness without having to worry about the availability of electricity during long-distance trips. Conversely, the marketing strategy for electric cars must shift from simply selling products to educating people about a new, sustainable lifestyle. Marketers must more actively promote long-term benefits such as significantly lower daily operating costs, instant, silent acceleration, and the convenience of being free from regional restrictions.